What Factors Influence the Sleep of On-call Workers?. Issue 2 (4th March 2021) - Vincent, Grace E.; Kovac, Katya; Signal, Leigh; Reynolds, Amy C.; Paterson, Jessica; Sprajcer, Madeline; Ferguson, Sally A.
ABSTRACT: Objective : On-call work is becoming increasingly common in response to service demands. This study had two aims; 1) describe the demographic profile of on-call workers in Australia, and 2) establish the impacts of on-call work on workers' sleep. Methods : A cross-sectional study was conducted using an online questionnaire completed by Australian on-call workers (n = 228) from various professions. The questionnaire included items on i) demographic and work characteristics, ii) rumination about on-call factors, iii) sleep quantity and quality. Analyses were conducted using mixed effects ordinal regression and multivariable logistic regression. Results : Workers slept <7 hours per night when on-call (80%), and reported sleep was impacted on-call even when no-calls were received (56%). On-call workers rated interruptions to family/leisure time (70%), missing a call (69%), preplanning in case of a call (69%), and not able to make plans (67%) as the main factors they ruminated about. Female on-call workers were more likely to think about the likelihood of being called, report frequent thoughts about what they would need to do if called, and think about interruptions to family/leisure time as a result of a call. Younger workers were more likely to think about the likelihood of being called compared to older adults, however middle-aged workers were less likely to plan for a call compared to younger workers. Conclusions : This study is the first to describe Australia's on-call population, including factors that specifically impact sleep. Future studies should implement tailored education and support strategies to address the unique challenges facing on-call workers.